Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/jcp.24465
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pivotal Cellular Factors Involved in HPV‐Induced Dysplastic and Neoplastic Cervical Pathologies

Abstract: Cervical carcinoma represents the paradigm of virus-induced cancers, where virtually all cervical cancers come from previous "high-risk" HPV infection. The persistent expression of the HPV viral oncoproteins E6 and E7 is responsible for the reprogramming of fundamental cellular functions in the host cell, thus generating a noticeable, yet only partially explored, imbalance in protein molecular networks and cell signaling pathways. Eighty-eight cellular factors, identified as HPV direct or surrogate targets, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…E2F1 also binds to the promoter of Cyclin A and regulated its expression, resulting in induction of S‐phase entry . E2F1 has been found to be deregulated in many types of cancers, including cervical cancer . E2F1 overexpression has been reported to promote cervical carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E2F1 also binds to the promoter of Cyclin A and regulated its expression, resulting in induction of S‐phase entry . E2F1 has been found to be deregulated in many types of cancers, including cervical cancer . E2F1 overexpression has been reported to promote cervical carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…47 E2F1 has been found to be deregulated in many types of cancers, including cervical cancer. 62 E2F1 overexpression has been reported to promote cervical carcinogenesis. 63 HPV E7 can bind and promote the degradation of retinoblastoma protein (pRb), resulting in the release of E2F1 from the pRb-E2F complex and thereby promote malignant transformation of cervical epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses in 2013 utilized a retrospective approach to identify novel genes involved in dysplastic and neoplastic cervical lesions, based on targets previously published in the literature [ 155 ]. The authors confirmed earlier results where FOXM1 , TOP2A , and E2F1 were not only overexpressed, but where their respective expression levels gradually increased as cervical lesions progressed from low-grade to high-grade lesions and eventually to carcinomas.…”
Section: Molecular Comparisons Between Cervical and Head And Neck mentioning
confidence: 99%
“…Other de-regulated genes included CDC25A , TP73 , and CCNE2 . Conversely, genes that demonstrated reduced expression in the progression from dysplastic tissue to carcinoma included PTGS2 , BCL2 , and FOS [ 155 ].…”
Section: Molecular Comparisons Between Cervical and Head And Neck mentioning
confidence: 99%
“…In addition, previous studies have found that ANGPTL4 is significantly associated with the susceptibility of CC, is a potential risk factor [ 30 ]. Muscular phosphofructokinase (PFKM), a member of the phosphofructokinase (PFK) family, can promote the growth of muscle-infiltrating bladder cancer [ 31 ] and can be used as a new breast cancer gene [ 32 ], and its expression level can distinguish normal tissues from CC tissues [ 33 ]. 6-Phosphofructo-2-kinase/fructose-2,6-biphosphatase 4 (PFKFB4), is a key kinase in Warburg pathway [ 34 ], has been found to be associated with a variety of cancers, including breast cancer [ 35 ], prostate cancer [ 36 ] and glioblastoma [ 37 ], promoting the progression and metastasis of cancer, and may become an effective molecular target of anti-tumor drugs.…”
Section: Discussionmentioning
confidence: 99%